To the History of M. V. Lomonosov’s “Russian Grammar”: Chronology, Versions, Collaborators - Natalia V. Kareva (Slovene, 2019)
The paper is an attempt to review and clarify data concerning Mikhail Lomonosov’s grammar studies and especially the history of his famous “Russian Grammar”. The authors lay out the timeline of its creation and publication. They describe the main steps on its way from the author to the reader and discuss evidence of its manuscript versions. Scholars know of at least four handwritten copies, none of which survive or have been identified. Only a few related drafts known as “Manuscript 112” or “Materials to the Russian Grammar” are available in the archive of the Russian Academy of Sciences (published in volume 7 of his Lomonosov's Complete Works). The article examines two parts of this manuscript which were apparently written not by Lomonosov: 1) lists of words and drafts of sections devoted to different parts of speech; 2) comments on some paragraphs of the “Russian Grammar”. Comparison of handwriting samples shows that the first part was not, as previously suggested, written by Lomonosov’s long-time assistant and copyist Ivan Barkov, while the second part was probably written by Lomonosov's classmate and fellow worker at the Academy Aleksey Barsov.